2023
DOI: 10.3390/ijms24032055
|View full text |Cite
|
Sign up to set email alerts
|

eIF4A1 Is a Prognostic Marker and Actionable Target in Human Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a primary liver tumor with high lethality and increasing incidence worldwide. While tumor resection or liver transplantation is effective in the early stages of the disease, the therapeutic options for advanced HCC remain limited and the benefits are temporary. Thus, novel therapeutic targets and more efficacious treatments against this deadly cancer are urgently needed. Here, we investigated the pathogenetic and therapeutic role of eukaryotic initiation factor 4A1 (eIF4A1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Its frequency is 6.8 per 100,000 in America, 5.5 per 100,000 in the west coast of Europe, and it increases up-to seventeen percent in Asia (Koulouris et al, 2021). According to the World Health Organization, liver cancer is becoming more common, and by 2030, it is expected to be responsible for over one million fatalities per year (Steinmann et al, 2023) .The majority of HCC cases are the result of prolonged liver damage induced by the hepatitis type B or C virus. Cirrhosis of the liver, of any cause, is adeterminant for causing liver Carcinoma (Prabhakar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Its frequency is 6.8 per 100,000 in America, 5.5 per 100,000 in the west coast of Europe, and it increases up-to seventeen percent in Asia (Koulouris et al, 2021). According to the World Health Organization, liver cancer is becoming more common, and by 2030, it is expected to be responsible for over one million fatalities per year (Steinmann et al, 2023) .The majority of HCC cases are the result of prolonged liver damage induced by the hepatitis type B or C virus. Cirrhosis of the liver, of any cause, is adeterminant for causing liver Carcinoma (Prabhakar et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The specific targeting of the translation machinery of proliferating tumor cells is a promising strategy to fight cancer. Steinmann et al identified the eukaryotic initiation factor 4A1 (eIF4A1) as a prognostic factor in hepatocellular carcinoma (HCC), whose molecular function can be suppressed by treatment with inhibitors [7]. These eIF4A1 inhibitors led to high antiproliferative and strong pro-apoptotic effects in HCC, and the anticancer activities of the eIF4A1 inhibitors were significantly augmented by the combination with a pan-mTOR inhibitor.…”
mentioning
confidence: 99%